PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN DI KABUPATEN MINAHASA SELATAN - Julio P.D. Ratag; Gene H.M. Kapantow; Caroline B.D. Pakasi (AGRI-SOSIOEKONOMI, 2016)
The aim of this research is to known the role of agricultural sector in South Minahasa Regency. The role was measured by sector position analysis and is the agriculture subsector was the base sector or nonbase by seeing the contribution of the agricultural sectorto the farming of Gross Regional Domestic Product in South Minahasa Regency. The data that has been used in this research was the secondary data by the Central Statistic Board of North Sulawesi Province, also the Agricultural and Livestock Service of South Minahasa Regency. The result of this research shows that the agricultural sector was the biggest contributor in the forming of GDRP in South Minahasa Regency. By using location quotient (LQ) analysis, the agricultural sector was one of the base sectors in the other sectors of econonomics, while agriculture subsector which was the base subsector is the one-season horticulture plants subsector. Based on the result of Dinamic Location Quotient (DLQ) analysis, the agricultural sector was predicted still be the base sector of South Minahasa Regency for five years ahead. Furthemore, the prediction of the agricultural subsector that have the potention of becoming the base subsector in the future is food plants subsector, one-sesion horticulture plants subsector, a-year horticultural subsector etcetera, a-year plantation subsector, livestock subsector, the service of agricultural subsector and hunting, and the fisheries subsector.